2022
DOI: 10.4014/jmb.2109.09054
|View full text |Cite
|
Sign up to set email alerts
|

Latilactobacillus curvatus BYB3 Isolated from Kimchi Alleviates Dextran Sulfate Sodium (DSS)-Induced Colitis in Mice by Inhibiting IL-6 and TNF-R1 Production

Abstract: Recent studies have shown that probiotics have health-promoting effects, particularly intestinal immune modulation. In this study, we focused on the immunomodulatory properties of Latilactobacillus curvatus BYB3, formerly called Lactobacillus curvatus, isolated from kimchi. In a mouse model of 14-day dextran sulfate sodium (DSS)-induced colitis, treatment with L. curvatus BYB3 significantly decreased the disease activity index, colon length, and weight loss. Moreover, histological analyses showed that L. curva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…In a mouse model of 14-day dextran sulfate sodium (DSS)-induced colitis, treatment with Lb. curvatus BYB3 significantly reduced the disease activity index, colon length, and weight loss [110]. Oral administration of Lb.…”
Section: Antimicrobial and Antioxidantmentioning
confidence: 92%
“…In a mouse model of 14-day dextran sulfate sodium (DSS)-induced colitis, treatment with Lb. curvatus BYB3 significantly reduced the disease activity index, colon length, and weight loss [110]. Oral administration of Lb.…”
Section: Antimicrobial and Antioxidantmentioning
confidence: 92%
“…Recent studies have identified the association between clinically relevant concentrations (1-10 ng/mL) of LPS and intestinal barrier dysfunction under in vivo and in vitro conditions (Guo et al, 2013). In our previous study, Latilactobacillus curvatus BYB3 decreased the disease activity score of dextran sulfate sodium-induced colitis in a mouse model (Wang et al, 2022). Supplementation with indole or using Lactobacillus reuteri with high AhR ligand production can improve some metabolic symptoms (Swimm et al, 2018).…”
Section: Introductionmentioning
confidence: 91%
“…EPS-producing L. curvatus strains can prevent the formation of Salmonella enterica serovar Eteritidis biofilm and effectively limit the colonization of pathogenic bacteria ( Redondo et al, 2017 ). In animal investigations, blood levels of IL-6, TNF-R1, TNF-R2, and TNF-α were considerably reduced in mice administered with L. curvatus BYB3, which improved DSS-induced intestinal inflammation ( Wang et al, 2022 ). Meanwhile, L. curvatus GH5L demonstrates antioxidant effects ( Düz et al, 2020 ).…”
Section: Therapeutic Effects Of Probiotics On Ucmentioning
confidence: 99%